Do parents implement pediatric neuropsychological report recommendations?. Issue 6 (9th July 2021) - Elias, John; Zimak, Eric; Sherwood, Andrea; MacDonald, Beatriz; Lozano, Nubia; Long, Jason; Larsen, A. Denise
Abstract: Objective: We explored parent-reported implementation rates of medical, home/community, and school recommendations following a pediatric neuropsychological evaluation, as well as demographic group differences in, and potential barriers to, recommendation implementation. Method: Participants were 55 parents of children and adolescents who completed an outpatient neuropsychological evaluation in a university-based hospital neuropsychology clinic within 4 to 6 months prior to study participation. Participants were contacted by phone to complete a short interview regarding implementation of report recommendations. Results: Slightly over half (52%) of all recommendations were implemented, with higher implementation rates of school (62%) and home/community recommendations (53%) than medical recommendations (40%). Results indicated significantly lower recommendation implementation for households with low income (particularly for medical recommendations). Reported reasons for not implementing recommendations included lack of time, lack of resources (geographical and financial), ambivalence about the need to implement the recommendation, not remembering the recommendation, confusion about how to implement the recommendation, and resistance from schools and teachers. Conclusions: The results for this study provide information for pediatric neuropsychologists regarding rates of recommendation implementation, with differences identified based on type of recommendation and demographic factors. Further empirical investigation is indicated in order to determine practical, concrete steps to improve recommendation implementation.